Preparation and evaluation of SEDDS of simvastatin by in vivo, in vitro and ex vivo technique. (August 2015) - Karim, Fahim Tamzeedul; Kalam, Azad; Anwar, Rafi; Miah, Muhammad Masum; Rahman, Md Shamim; Islam, S. M. Ashraful
Abstract The objective of this work was to formulate a Self Emulsifying Drug Delivery System (SEDDS) of simvastatin, a poorly soluble drug and to evaluate by in vivo, in vitro and ex vivo techniques. Oils and surfactants were screened out depending upon their solubilizing capacity. Among all of the solvents, Capryol 90 showed good solubilizing capacity. It dissolved 105 mg/ml of simvastatin. Tween-80 also showed good solubilizing capacity which was 117 mg/ml. The two excipients were used to prepare simvastatin SEDDS. Formulations were initially checked for the color, clarity and sedimentation. The SEDDS formulations were transparent and clear. Formulation F2 containing 7:3 (m/m) mixture of Capryol 90/Tween-80 produced smallest micro-emulsion with particles size of 0.074 µm and drug release was higher than other formulation (102% within 20 min). Ex vivo study of the SEDDS formulation was evaluated using guinea pig intestinal sac. Drug diffused from F2 formulation was significantly higher than pure drug (p < 0.001). In vivo study of SEDDS was performed in albino mice using plasma cholesterol level as a pharmacodynamic marker parameter. The test formulation (F2) appeared remarkable reduction in plasma cholesterol level, after oral administration which showed that SEDDS may be an effective technique for the oral administration of simvastatin.